Body City Car Design of Two Passengers Capacity: A Numerical Simulation Study - Randi Purnama Putra; Dori Yuvenda; Andrizal Andrizal; Martias Martias; Muji Setiyo (Universitas Muhammadiyah Magelang, 2022)
A city car is needed to overcome congestion and parking spaces in urban areas. However, currently, the body design of the city car is still experiencing problems, namely the value of the large drag coefficient, which causes an increase in fuel consumption. This study aims to design a city car body with two passengers that is more aerodynamic so as to minimize fuel use. This research method is a numerical simulation model using the ANSYS fluent students version 2021. Parameters in the form of drag coefficient values, velocity streamlines and velocity contours on the city car are aerodynamic aspects that are analyzed. The results show that the dimensions of the designed city car have a length of 2.59 m, a width of 1.6 m, and a height of 1.52 m by considering the ergonomic parameters and comfort of the user so that it fits the character of the people in Indonesia. In addition, from the independence grid analysis performed, the value of the number of meshes that have the smallest error value is obtained, namely mesh C (the number of meshes is 129,635). Mesh C has an error of 7.2%. It was found that as the velocity increases, the value of the drag coefficient (CD) produced is relatively smaller. In a city car with a velocity of 10 m/s, the drag coefficient value is 0.599, at a velocity of 20 m/s, the drag coefficient value is 0.594, and a velocity of 30 m/s is a drag coefficient value of 0.591.